PENCARIAN JATI DIRI DALAM NOVEL SELAMAT TINGGAL KARYA TERE LIYE (ANALISIS SASTRA CARL THOMPSON) - Julaila; Elsa Mulya Karlina (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2026)
The search for identity is a crucial process experienced by individuals in understanding their identity, life values, and purpose. This phenomenon is widely represented in literary works, one of which is Tere Liye's novel Selamat Tinggal. This study aims to describe the forms of identity search experienced by the main character and explain the process of identity search based on Carl Thompson's theory. The study employed a qualitative descriptive method with library research. The primary data source was Tere Liye's novel Selamat Tinggal, while secondary data sources were obtained from books, journals, and relevant previous research. Data collection techniques used reading and note-taking, while data analysis utilized content analysis. The results show that the main character's search for identity is manifested through moral awareness, education, self-awareness, and social interaction. Furthermore, the process of identity search occurs through life experiences, inner conflict, self-reflection, changes in perspective, and the formation of a new identity. Based on Carl Thompson's perspective, the character's journey is not merely a physical displacement, but an inner journey that results in identity transformation. Thus, the novel Selamat Tinggal contains moral values, character education, and life reflections that are relevant to society.